2018
DOI: 10.1017/s1049023x18000481
|View full text |Cite
|
Sign up to set email alerts
|

The Great East Japan Earthquake, Tsunamis, and Fukushima Daiichi Nuclear Power Plant Disaster: Lessons for Evidence Integration from a WADEM 2017 Presentation and Panel Discussion

Abstract: In April 2017, some of the health impacts of the 2011 Great East Japan Earthquake, tsunamis, and resultant Fukushima Daiichi nuclear power plant disaster (Okuma, Fukushima Prefecture, Japan) were presented at the 19th Congress of the World Association for Disaster and Emergency Medicine (WADEM; Madison, Wisconsin USA) in Toronto, Canada. A panel discussion was then opened by asking audience members about their experiences in their own countries, and how they would suggest taking steps to reach the goals of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The NPP accident was not a simple event of radiation and contamination: it was a combination of a series of events including mass evacuation, job losses, dangerous rumors and an aging population, among others, all of which may lead to health deterioration ( Fig. 2 ) [ 3 ]. Overall, experts tended to focus too much on radiation and cancer instead of appreciating a holistic view of health.…”
Section: Discrepancy In Views Of a Disastermentioning
confidence: 99%
See 1 more Smart Citation
“…The NPP accident was not a simple event of radiation and contamination: it was a combination of a series of events including mass evacuation, job losses, dangerous rumors and an aging population, among others, all of which may lead to health deterioration ( Fig. 2 ) [ 3 ]. Overall, experts tended to focus too much on radiation and cancer instead of appreciating a holistic view of health.…”
Section: Discrepancy In Views Of a Disastermentioning
confidence: 99%
“…The 2011 Fukushima Daiichi Nuclear Power Plant (NPP) accident was one of the largest CBRNE disasters in world history. It occurred in a society in which information was highly networked, and misunderstandings of health risks were potentially exacerbated by media outlets [ 3 ]. Such ‘media hype’ engendered public stigma against Fukushima immediately after the disaster [ 4 ] and interrupted channels of supply over a wide area around the NPP [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in Japan, medical exposure exceeds exposure to natural radiation, indicating that high levels of medical exposure are remarkable worldwide. Japanese people experienced the Hiroshima and Nagasaki atomic bombings, the Tokaimura nuclear accident (the Japan Nuclear Fuel Conversion Co. criticality accident) [5], and the Fukushima Daiichi Nuclear Power Plant accident [6][7][8][9][10][11][12][13][14][15]; therefore, medical radiation exposure is likely to be of significant concern [16,17]. The Fukushima Daiichi Nuclear Power Plant accident was a nuclear disaster that affected a wide area of eastern Japan, and many people outside of Fukushima Prefecture also suffered from anxiety about disaster exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, resilience to nuclear disasters emerged as a core public health challenge. Japan’s Fukushima nuclear disaster in 2011 not only showcased fundamental weaknesses in the country’s preparedness and responses to nuclear emergencies, but also highlighted the importance of focusing more attention on the management of nuclear disasters—at individual, community, and policy levels—in global disaster debates [ 1 ]. The challenges of the Fukushima disaster have shown that national and global policies on nuclear disaster management are in urgent need of reform and reinforcement.…”
mentioning
confidence: 99%